An Interpretative Phenomenological Analysis study exploring the experiences of post-16 education for separated young people seeking safety in the UK. - Nielsen, Barbara (2023)
This research is set at a time when the number of people who have been forcibly displaced is rapidly rising, forcing thousands of separated young people to travel without the support of an adult, to seek safety in another country. Separated young people seeking safety have been found to experience difficulties in their resettlement in the UK, where young people aged between 16-18 years are noted to be particularly vulnerable. Research has highlighted the important role that systems around separated young people can play in supporting positive outcomes in resettlement, such as education. However, there is a lack of consideration given to the voice of separated young people seeking safety in their education, which appears to render them invisible in educational policy and practice. To address this gap, qualitative, exploratory research was undertaken. This research aimed to explore the experiences of post-16 education for separated young people seeking safety in the UK. It sought to give voice to their individual lived experiences through an Interpretative Phenomenological Analysis methodology. Semi-structured interviews were completed with five separated young people. Interpretation of the data highlighted four interconnected Group Experiential Themes: importance of developing English proficiency, aspirations for the future, sense of agency and sense of belonging. These themes are explored in relation to existing research and psychological theories. This research also offers unique interpretations, including the importance of an emotionally safe space to develop English proficiency, differences in experiences between forms of post-16 educational provision, and the need for guidance when navigating post-16 pathways that engage with separated young people’s high aspirations and desire for independence. Limitations of the research are considered, before highlighting implications for the practice of Educational Psychologists, including their role in promoting the distinct needs of separated young people seeking safety in education.